OPTIMIZING PARENTAL INVOLVEMENT IN EDUCATION OF LEARNERS WITH AUTISM IN ESWATINI MAINSTREAM PRIMARY SCHOOLS - Mamba, Agnes Tholakele; Maseko, Nonhlanhla Desiree (International Journal of Humanity Studies (IJHS), 2024)
In 2010, the Kingdom of Eswatini granted learners with mild to moderate forms of autism the right to access education in neighborhood schools. However, the Eswatini Annual Education Census report of 2019 did not make specific mention of these learners current state of affairs. This qualitative, phenomenological study explored strategies for optimizing parental involvement in the education of learners with autism in Eswatini mainstream primary schools. The data were extracted through interviews and document analysis from fifteen purposively sampled parents and teachers selected from four mainstream primary schools in Eswatini. The data were analyzed thematically. Ethical considerations upheld during this investigation were informed consent, voluntary participation, anonymity, and confidentiality of information that participants divulged. One major finding of this study demonstrates that thedeployment of highly autism-qualified teachers is crucial for laying a concrete foundation for parents to use in helping the learners in theirstudies. Thus, to accrue theinvolvement of parents in education, the Deputy Prime Ministers office should state guidelines and craft monitoring tools to ensure that schools embrace and support the involvement of parents.